2014
DOI: 10.1186/1471-2105-15-113
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic drug connectivity mapping

Abstract: BackgroundThe aim of connectivity mapping is to match drugs using drug-treatment gene expression profiles from multiple cell lines. This can be viewed as an information retrieval task, with the goal of finding the most relevant profiles for a given query drug. We infer the relevance for retrieval by data-driven probabilistic modeling of the drug responses, resulting in probabilistic connectivity mapping, and further consider the available cell lines as different data sources. We use a special type of probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…The study found the PI3K inhibitor LY294002 to be significantly effective in reversing prednisoloneresistance profile and induce sensitivity [51,62]. Moreover, the prednisolone-sensitizing effects of LY294002 on two cell lines studied consist of five downregulated genes, namely PARVB, A probabilistic connectivity mapping by [41] was introduced as a modelbased alternative to the original CMap. The method uses a probabilistic model that focuses on the relevant gene expression effects of a drug as a probabilistic latent factor derived from the data on cell lines.…”
Section: Discovering Novel Phenotypic Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found the PI3K inhibitor LY294002 to be significantly effective in reversing prednisoloneresistance profile and induce sensitivity [51,62]. Moreover, the prednisolone-sensitizing effects of LY294002 on two cell lines studied consist of five downregulated genes, namely PARVB, A probabilistic connectivity mapping by [41] was introduced as a modelbased alternative to the original CMap. The method uses a probabilistic model that focuses on the relevant gene expression effects of a drug as a probabilistic latent factor derived from the data on cell lines.…”
Section: Discovering Novel Phenotypic Relationsmentioning
confidence: 99%
“…Parkkinen et al [41] showed their proposed probabilistic connectivity mapping method is capable of identifying drug combinations. Specifically, they define a combined drug profile consisting of drug pairs by assessing the correlation of their individual profiles.…”
Section: Drug Combinationsmentioning
confidence: 99%
“…AstraZeneca-Sanger Drug Combination DREAM Challenge was launched using 85 cancer cell lines and 11,759 drug combination screening for 118 drugs [8]. The predictive models were designed to differentiate synergistic, additive and antagonistic combinations and predict new synergistic combinations in silico [9][10][11][12][13][14][15][16][17].…”
Section: Mathematical Optimization Methodsmentioning
confidence: 99%
“…Parkkinen and Samuel's method [14] extends the original CMap's methodology [19]. They matched the pattern of drug perturbation profiles from multiple cell lines.…”
Section: Unsupervised Methodsmentioning
confidence: 99%
See 1 more Smart Citation